HAEMOGLOBINURIA AND PORTAL VENOUS THROMBOSIS IN A YOUNG MALE - Abideen, Zain ul; Jafar, Munnam Sohail; Hameed, Nasir; Malik, Ahmad (Journal of Ayub Medical College Abbottabad, 2017)
Paroxysmal nocturnal haemoglobinuria is a non-malignant stem cell disorder due to acquired somatic mutations in cell surface anchored proteins CD55 and CD59. Both have a compliment inhibitory role and their deficiency leads to intravascular haemolysis. This paper reports a challenging case of a 25 years old male who presented with generalized weakness, exertional dyspnoea and episodic early morning haematuria. Recently, he started developing progressive abdominal distention and dull generalized abdominal pain. Investigations revealed haemoglobin 3.5g/dl with 10% reticulocytes, total bilirubin 54.5 mg/dl, LDH 3155 U/L, negative Coomb’s test and erythroid hyperplasia on bone marrow biopsy. Urine complete exam was significant for haemoglobinuria without red blood cells. Doppler scan of abdomen showed portal vein thrombosis. Loss of expression of CD14, CD16, CD55 and CD59 on leukocytes and erythrocytes was seen on PNH analysis, confirming paroxysmal nocturnal haemoglobinuria. He was managed with blood transfusions and was advised folic acid and bone marrow transplant. Keywords: Paroxysmal nocturnal haemoglobinuria; Portal venous thrombosis; Haemolysis, Haemoglobinuria